Biaya Kemacetan Dan Polusi Karbon Monoksida Pada Lalu Lintas Akibat Adanya Pembangunan Fly –Over (Studi Kasus: Fly-Over Simpang Jalan Ahmad Yani–Gatot Subroto Kota Banjarmasin) - Hayati, Fatia Mufieda; Wicaksono, Achmad; Sutikno, Fauzul Rizal (Fakultas Teknik, Universitas Brawijaya, 2013)
Traffic congestion is one problem in Banjarmasin. Congestion in Banjarmasin. Congestion in Banjarmasin also supported by a 38% increase in the number of vehicles within the last 5 years.This encourage the government of Banjarmasin to plan a strategy to reduce congestion level in Banjarmasin. One of the solution from the goverment is fly over construction. The located of fly over construction in Ahmad Yani-Gatot Subroto street. The aim this study to identify disadvantage congestion cost and carbon monoxide air pollution cost in traffic when there is fly over contruction. This study can be used to consider the next traffic management. So, it can minimize the congestion impact. This research is using Tzedakis,1980. By calculation component is traffic volume, vehicle speed, vehicle operating costs, and vehicle queuing time.method to calculate congestion cost. The result of calculation congestion cost is Rp. 332.925.803/day. Moreover this research using litmann method, asif faiz method, and world bank method to calculate carbon monoxide air pollution cost. this study compare between the third method and existing air test, to get air pollution result exactly. Asif faiz Method is the best to apply in this research. The result of calculate disadvantage to air polution cost is Rp. 907,588,348/day. enhancement to congestion cost when fly over construction on process is 76% and air pollution cost is 67%.Keywords: Congestion Cost, Air Pollution Cost